2019
DOI: 10.1088/1612-202x/ab44b8
|View full text |Cite
|
Sign up to set email alerts
|

Energy band splitting and high-order harmonic generation from a doped semiconductor

Abstract: We theoretically investigate the high-order harmonic generation (HHG) from laser-solid interaction in a doped semiconductor by solving the one-dimensional time-dependent Schrödinger equation within the single active electron model. The results show that the energy band of the valence and the low conduction band can be split into a small band in the doped semiconductor. The splitting band gap can be controlled by changing the depth of the potential well of the doped semiconductor, and the second HHG plateau can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Another significant effect of the doping is the appearance of point defects such as vacancies and interstitial sites 28,29 . According to recent theoretical investigations dopant-induced band-gap changes can substantially influence the HHG process [29][30][31][32][33] . In particular, donor-doped materials were theoretically predicted to enhance the HHG yield due to electronic excitation from impurity states 31,33 We here investigate the influence of dopant-induced vacancies on the HHG yield in chromium-doped magnesium oxide (MgO:Cr), which was extensively studied previously using experimental [34][35][36][37] and numerical [38][39][40] methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another significant effect of the doping is the appearance of point defects such as vacancies and interstitial sites 28,29 . According to recent theoretical investigations dopant-induced band-gap changes can substantially influence the HHG process [29][30][31][32][33] . In particular, donor-doped materials were theoretically predicted to enhance the HHG yield due to electronic excitation from impurity states 31,33 We here investigate the influence of dopant-induced vacancies on the HHG yield in chromium-doped magnesium oxide (MgO:Cr), which was extensively studied previously using experimental [34][35][36][37] and numerical [38][39][40] methods.…”
mentioning
confidence: 99%
“…Other future studies will concentrate on HHG spectroscopy to extract information on the intrinsic properties of light-driven attosecond electron transport 69 . This would create attractive perspectives towards the development of all-solid-state attosecond sources and petahertz electronics [12][13][14][29][30][31][32][33]55 .…”
mentioning
confidence: 99%
“…Therefore, one can expect substantial changes of the HHG yield due to modifications of the band gap. This fact has recently raised interest among theoretical works on the use of doped materials for the HHG [26][27][28][29] . For instance, the effect of impurity levels on the HHG is discussed in the theoretical investigations exploiting time-dependent density functional theory 27 , where the authors have shown the enhanced HHG yield from the donor-doped material due to the electron tunneling from the impurity states to the conduction band.…”
Section: B Hhg From Solids With Defectsmentioning
confidence: 99%
“…It is due to the high electronic density and periodic structure in crystals [5][6][7]. Some novel phenomena from Block electrons in solids, such as ellipticity dependence [8][9][10], multiplateau structure [11,12] et al, can be found in previous the multi-band systems in periodic potential. The main features of the HHG in solid can be captured by the SBEs model, which can be used to investigate the real systems.…”
Section: Introductionmentioning
confidence: 99%